MADZHAB LINTAS TAFSIR KONTEMPORER - Diyah Pratiwi; Angga Rohmandani; Nur Syafiqoh Binti Nahlil; Abdul Rouf (STKIP Subang, 2025)
The development of contemporary Qur’anic interpretation has generated diverse methodological approaches, resulting in various schools of tafsir with textual, contextual, rational, and thematic tendencies. While this diversity enriches Islamic intellectual discourse, it also poses the risk of fragmented religious understanding. Therefore, an integrative approach is needed to bridge these differences through the framework of cross madhhab contemporary tafsir. This study aims to analyze the concept, characteristics, and relevance of cross madhhab tafsir in addressing contemporary intellectual and socio religious challenges. The research employs a qualitative method with a library research approach, utilizing content analysis and comparative analysis of contemporary tafsir works across different schools. The findings reveal that cross madhhab contemporary tafsir emphasizes dialogical, integrative, and moderate principles in understanding the Qur’an, accommodating multiple interpretive approaches without undermining textual authority. In conclusion, cross madhhab contemporary tafsir represents a strategic approach to fostering inclusive, contextual, and relevant Islamic understanding in response to the dynamics of modern society.